EPISTEMOLOGI ISLAM Vs BARAT DI ERA KECERDASAN BUATAN: TELAAH FILOSOFIS-ETIS ATAS TRANSFORMASI PENDIDIKAN - Sulhatul Habibah; Ahmad Nur Fuad (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This study stems from the development of artificial intelligence (AI), which has brought about radical transformations in education. AI is not merely a tool to assist in the learning and administrative processes, but also raises epistemic crises related to the authority of knowledge, the validity of truth, and ethical dimensions. Western epistemology, which is empirical-positivistic in nature, tends to place AI as a neutral and efficient instrument for the production of knowledge, but risks giving rise to reductionism and dehumanization. Meanwhile, Islamic epistemology, with its bayān, burhān, and ‘irfān frameworks, offers a transcendental foundation that links knowledge with moral, spiritual, and social responsibility values. This study uses the library research method with a comparative philosophical approach. The purpose of this study is to trace the relevance and limitations of both epistemologies in responding to the penetration of AI into educational practices. The discussion shows that Western epistemology is efficient in explaining the technical-instrumental aspects of AI, while Islamic epistemology is able to provide a normative and ethical framework to guide its use. This study argues for the need for a transcendental integrative epistemological model, in which AI is understood as a space of synthesis between empirical reason and spiritual-transcendental values.